NegotioPoly: A holistic gaming approach to negotiation teaching - Tuvana Rua; Zeynep Aytug; Leanna Lawter (Organization Management Journal (OMJ), 2022)
Purpose Based on Behavioral Theory of Negotiations (Walton & McKersie, 1965), the purpose of this paper is to discuss the existing gap between negotiation theory and pedagogy and presents an experiential teaching tool that closes this gap. The tool is a 'serious game' (Abt, 1975) that reinforces all four core negotiation subprocesses while allowing students to practice their negotiation skills and several critical business competencies in a realistic and improvisational context. Design/methodology/approach After successfully using NegotioPoly for five years, qualitative and quantitative data were collected in three sections of negotiation classes to assess student learning and behaviors while playing NegotioPoly and to collect student feedback on the effectiveness of NegotioPoly in teaching and reinforcing key negotiation skills. Findings Findings support that NegotioPoly is highly effective in engaging students in a series of realistic negotiations, joint problem solving and strategic decision-making. Results show that, during the game, students demonstrate their negotiation skills and learnings, and they practice all four negotiation subprocesses of distributive, integrative and intraorganizational bargaining and attitudinal structuring. Practical implications NegotioPoly enables students to engage in distributive and integrative bargaining, multiple levels of negotiations and coalitions in quick succession. Students practice organizational politics and adjust their negotiations based on relationships and social realities, as they demonstrate advanced deal-making behaviors and core business competencies of problem solving, decision-making, analytical skills and ability to work with others. Social implications NegotioPoly reinforces core business competencies such as negotiation, problem solving, analytical skills and the ability to work in teams that employers look for and, therefore, is a useful tool for preparing students for the business world. Originality/value NegotioPoly is an experiential learning tool that closes the gap between negotiation theory and pedagogy while providing deep learning and realistic practice opportunities for students where they can use their negotiation skills in a gaming environment that uses multi-party and multi-round negotiations.
Keywords: 650; Behavioral theory of negotiations; Negotiation subprocesses; Multi-party negotiation; Multi-round negotiation; Game-based learning